Hubungan Antara Dukungan Suami Dengan Tingkat Kecemasan Pada Pasien Kanker Serviks Yang Menjalani Kemoterapi Di Rumah Sanglah Pada 2013 - Luh Putu Suyanti; Ni Gusti Ketut Sriasih; Ni Wayan Armini (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2018)
Chemotherapy that as the treatment by patients with cervical cancer can cause anxiety. High anxiety can impede the healing process. Support by husband is the one that can overcome the anxiety. The purpose of this study was to determine the relationship of husband support to level of anxiety in patient with cervical cancer will be has chemotherapy at Sanglah Hospital . This type of research is an observational study with cross sectional approach . The number of sample was 35 people were selected through purposive sampling. Analysis with Spearman Rank Test found probabilitas value is 0.01 this value 0.05, Conclution is a relationship between a husband support to anxiety in patient with cervical cancer will be has chemotherapy. Correlation koeficien value is -0.63 its means with higher husband's support, cause lower of level of anxiety in patient with cervical cancer will be has chemotherapy and the relationship is strong. It is expected that health workers in Sanglah Hospital providing information to improve husband support for reduce level of anxiety in patient with cervical cancer will be has chemotherapy and increasing the healing process.